Farmers brush up indigenous crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Cultivation of indigenous crops was neglected during the apartheid era in South Africa, but in June 2000, farmers from the Umbumbulu community delivered the first crates of amadumbes (Colocasia esculenta) to Pick n Pay, a South African retailer....